Cyber-Physical Systems - Silva, Edgar M. (2021)
This research work was partially supported by funds provided by the European Commission in the scope of FoF/H2020-636909 C2NET, FoF/H2020-723710 vf-OS and ICT/H2020-825631 ZDMP.